Recent advance in patient-specific 3D printing templates in mandibular reconstruction. (June 2020) - Lu, Tingwei; Shao, Zhe; Liu, Bing; Wu, Tianfu
Abstract: Patient-specific 3D printing template is used in mandibular defect reconstruction with multiple deficiencies. During the operation, the template can accurately transfer the preoperative design, assisting surgeons to complete the surgery with high efficiency and accuracy. The template design has been continuously improved to obtain good application for miscellaneous classification and description. This review attempted to preliminarily analyse and summarise recent advancements in personalized 3D printing templates in mandibular reconstruction from the aspects of functional classification, existing problems, improved strategies and post-surgery evaluation by reviewing studies and through our combined clinical work and experience on hundreds of reconstruction surgeries. Highlights: Templates that used in mandible reconstruction were classified into three categories according to their functions. We summarised some specific designs that are the keys to improve the accuracy of templates. We came up with existing problems of templates and relative solutions to deal with. The accuracy of operations that using different templates were listed.